Role of smart technology use behaviour in enhancing tourist revisit intention: the theory of planned behaviour perspective - Zheng, Kundan; Kumar, Jeetesh; Kunasekaran, Puvaneswaran; Valeri, Marco (Emerald, 2022)
This study examines the influencing factors of smart technology use behaviour (STUB), influencing tourist satisfaction and enhancing revisit intention for the Chinese tourism destination. Further, the moderating role of place attachment on the relationship between STUB, tourist satisfaction and revisit intention has been examined.The study employs quantitative methodology by incorporating the planned behaviour theory to develop the hypotheses. Using an online survey link, 409 responses were collected from the tourists employing a non-probability convenience random sampling technique.The partial least squire-structural equation modelling (PLS-SEM) results show that social influence significantly affects STUB, tourist satisfaction and revisit intention. Also, the anticipated positive behaviour has positive and significantly affects STUB and revisit intention. Finally, the findings show that tourist satisfaction significantly affects revisit intention in the tourist destinations in China.A quantitative research design was applied, employing a random sampling technique, and surveys were conducted with tourists only in current research. However, future research can incorporate a wide range of methodology by collecting data from other tourism stakeholders to have an in-depth evaluation of repeat visitation behaviour. Future research can enhance the current conceptual framework by including other relevant variables like negative anticipated emotions at other locations, as the current study was conducted in the Chinese context.This research adds value to the tourism destination to formulate tourist satisfaction and revisit intention. Implications are provided for a more nuanced understanding and effective planning in tourism destinations while considering smart technology use.